2001
DOI: 10.1074/jbc.m101113200
|View full text |Cite
|
Sign up to set email alerts
|

Flotillin-1-enriched Lipid Raft Domains Accumulate on Maturing Phagosomes

Abstract: Flotillin-1 was recently shown to be enriched on detergent-resistant domains of the plasma membrane called lipid rafts. These rafts, enriched in sphingolipids and cholesterol, sequester certain proteins while excluding others. Lipid rafts have been implicated in numerous cellular processes including signal transduction, membrane trafficking, and molecular sorting. In this study, we demonstrate both morphologically and biochemically that lipid rafts are present on phagosomes. These structures are enriched in fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
230
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(253 citation statements)
references
References 41 publications
17
230
1
1
Order By: Relevance
“…Consistent with the results obtained by confocal immunofluorescence microscopy, we found reduced levels of LAMP-1 in phagosome extracts from SHP-1 deficient at all time points tested. Flotillin is recruited to phagosomes from compartments distinct from those bearing LAMP-1 (35). As shown in Fig.…”
Section: Shp-1 Is Recruited To Nascent Phagosomes and Remains Throughmentioning
confidence: 94%
See 1 more Smart Citation
“…Consistent with the results obtained by confocal immunofluorescence microscopy, we found reduced levels of LAMP-1 in phagosome extracts from SHP-1 deficient at all time points tested. Flotillin is recruited to phagosomes from compartments distinct from those bearing LAMP-1 (35). As shown in Fig.…”
Section: Shp-1 Is Recruited To Nascent Phagosomes and Remains Throughmentioning
confidence: 94%
“…Little is known concerning the mechanism(s) regulating the phagosomal recruitment of the v-ATPase as well as the regulation of its activity. Previous studies revealed that phagosomal acidification starts early during phagosome formation, before acquisition of lysosomal features such as LAMP-1 and cathepsins (8,53,54), which are recruited to phagosomes through distinct kinetics and mechanisms (7,35,55). Recently, it was shown that early recruitment of the a3 subunit of the v-ATPase to young phagosomes occurs via tubular structures extending from the perinuclear lysosomes along microtubules (56).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a striking sequence similarity between flotillin-1 and flotillin-2, specific recruitment of flotillin-1 to lipid bodies upon fatty-acid loading could also underline a specific function in lipid regulation or trafficking towards these organelles. Flotillin-1, but not flotillin-2, has been shown to be enriched in maturing phagosomes (Dermine et al, 2001) and exosomes (Rajendran et al, 2006), and only flotillin-1 is specifically upregulated at least 10-fold during adipocyte differentiation (Bickel et al, 1997), suggesting that flotillin-1 could be involved in storage pathways. Finally, another possibility is that flotillins could function as a raft organizer by means of homo/hetero-oligomerization (Neumann-Giesen et al, 2004), and thus would organize or shape scaffold domains at the level of lipid droplet membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally we note the induction of flotillin-1 (Fig. 2), a protein that is enriched in lipid rafts (44), which are membrane structures that facilitate fusion of HIV with plasma membranes of target cells (45). Discussion HIV-1 pathogenesis is regulated by a complex interaction between viral and cellular factors.…”
Section: Gp120-mediated Modulation Of a Group Of Genes Involved In Mem-mentioning
confidence: 99%